(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
The state considers the role of a sports club in the formation of a pre-dolor lifestyle among students, physical development, healthy behavior, as well as topical issues, such as the culture of a pre-doro lifestyle. It presents scientific and methodological indicators based on the analysis of the accumulated experience on the pre-prenatal lifestyle based on the results of a questionnaire tested among the participating family education systems.